Analisis Break Event Point (BEP) Sebagai Alat Perencanan Laba Jangka Pendek Pada UMKM Cafe Limas Palembang - Sinta Agustiani Putri; Eka Jumarni Fithri (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This final report is made to help performing profit planning with fixed costs and variable costs as a basis in doing profit planning using Break Even Point (BEP). The title of this final report is "Break Even Point Analysis As A Short Term Profit Planning Tool at UMKM Café Limas Palembang". In completing this final report the authors obtained data by conducting field research through interviews and observation, library research. Based on the data that the author obtained, the company has not done separation of fixed costs and variable costs, so the company does not know how much fixed costs and variable costs, calculation of Break Even Point (BEP) and Margin of Safety (MOS) calculation, which are useful as a tool of corporate profit planning. The author suggests that company should classify fixed costs and variable costs in advance in order to perform calculation of Break Even Point (BEP), calculation of Margin of Safety (MOS) and profit planning.